A decomposição da soma de quadrados do resíduo (a) numa análise de variância de ensaios em parcelas subdivididas, no caso em que nem todos os tratamentos principais tem tratamentos secundários - Regazzi, Adair José; de Campos, Humberto (Revista Ceres, 2025)
The partitioning of the error sum of squares in components corresponding to comparisons of the interest is one of the recommended procedures to solve the heterogeneity of variance problems of the irregular type. This paper shows how to obtain specific errors for each contrast of interest among the main treatments, through a method based on the linear transformation theory, i.e., orthogonal transformations.